Bibliometric Analysis in Mapping Corporate Marketing Research Trends and Developments - Maharani, Dewi; Yuswono, Irawan; Sutono, Sutono; Junianto, Pilifus (West Science Journal Economic and Entrepreneurship, 2023)
This research conducts a comprehensive bibliometric analysis to map the trends and developments in corporate marketing research, utilizing data from a diverse range of publications. Through theme analysis, influential publications, and keyword occurrences, the study unveils the multifaceted nature of the field. The most prevalent themes include Corporate Marketing, Green Marketing, Reputation, Communication, and Relationship Marketing, reflecting the dynamic interplay of strategic elements within corporate marketing. Noteworthy publications, such as "Principles of Corporate Finance" and "Corporate Social Responsibility: A Theory of the Firm Perspective," emerge as key influencers, shaping the intellectual discourse in the domain. The integration of these findings provides valuable insights for researchers, practitioners, and policymakers, offering a nuanced understanding of the current state of corporate marketing research. As the field continues to evolve, this research sets the stage for future inquiries, providing a foundation for strategic decision-making and ongoing scholarly exploration.